The Words â€œSuspectâ€ and â€œPatientâ€: A Corpus-Based Analysis of Semantic Prosody in COVID-19 Corpora - Purwitarini, Dhyan (OKARA: Jurnal Bahasa dan Sastra, 2020)
At present, we often encounter the use of the words 'suspect' and 'patient' in various discussions of the COVID-19 pandemic. In this case, the writer is eager to identify the frequency of using the words 'suspect' and 'patient' in the COVID-19 corpus and to explain the significant collocates based on the frequency score whether they are in a positive or negative sense. The two words are selected because they are identical synonyms which frequently used during the COVID-19 pandemic. This study applied the qualitative method with the COVID-19 data instrument through a sketch engine and used a corpus approach. The analysis results are how the word tokens from the synonym 'suspect' and 'patient' are described in the context of COVID-19 data. The word 'suspect' in the COVID-19 corpus shows collocation with the results of 14,505 (51.66 per million) and the word 'patient' with the number 518,618 (1,847.18 per million). The word 'patient' is more widely used in scientific research on the topic of COVID-19 than the word 'suspect'. Based on the semantic prosody, the words that follow the word 'suspect' are collocating negative tendencies. Conversely, words that follow the word 'patient' have collocates with a positive tendency